Peran Rumah Yatim Dalam Membantu Kehidupan Rumah Tangga Masyarakat Miskin di Kota Medan - Ariel Miansyah B Manalu; Waizul Qarni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
A poor household is a condition in which the individual is unable, namely based on his economy in meeting his daily needs based on the average standard of living in the general public in a certain area. This inadequacy situation is due to the low daily income in meeting secondary and tertiary needs. This low income will certainly result in a reduced ability to meet the average standard of living, such as public health and education. know in depth about the role of the Orphan House in Helping Poor Households in Medan City. The research method used is interviews and literature review or literature review. In this study, assistance from orphanages can ease the burden on poor households and the poor must be very helpful because of the many aid programs from orphanages. The Ar-Rahman orphanage assistance program is assistance in the fields of animal husbandry, agriculture, plantations and other programs that Of course, it is very beneficial for the poor and underprivileged in financing their lives, even though there are obstacles in its implementation, but the orphanage assistance program must continue to be carried out. Keywords: Orphans, Community, and Poor